Pengaruh Model Pembelajaran Berbasis Proyek terhadap Kemampuan Berpikir Kritis Siswa SMK: Sebuah Tinjauan Literatur - Enjang Suhaedin; Rozali Ilham; Ambiyar Ambiyar; Riski Ema Wulan Sari (Journal on Education, 2024)
The project-based learning model (Project-Based Learning, PBL) has been implemented in Vocational High Schools (SMK) with the aim of improving the quality of learning and student learning outcomes, especially in terms of critical thinking skills. This research aims to explore the implementation of PBL, identify the challenges and obstacles faced, and analyze its impact on student learning outcomes. The research method used is a literature review which examines various studies and articles related to PBL in vocational schools. The research results show that the implementation of PBL in vocational schools has a positive impact on increasing students' engagement, learning motivation and critical thinking abilities. Students who engage in PBL show improvements in analytical, evaluative, and problem-solving abilities. However, there are various challenges that hinder the effective implementation of PBL, including limited resources, teacher readiness and competency, assessment complexity, and lack of institutional support. To overcome these challenges, increased training and support for teachers, development of infrastructure and resources, and stronger institutional support are needed. In addition, flexibility in the curriculum and strengthening the assessment system are also important to ensure the success of PBL. By overcoming these obstacles, PBL can be an effective learning method in developing vocational school students' critical, creative and collaborative thinking skills, preparing them for challenges in the world of work and real life.